'A Curst Little Jew from Duke's Place': Daniel Mendoza and the Folkloric Representation of the Jew in Georgian England. Issue 4 (2nd October 2022) - Bell, Michael J.
Abstract: At the end of the eighteenth century, Daniel Mendoza (1764–1836), a five-feet-seven, 160-pound bare-knuckle Jewish fighter, rose to become the world's heavyweight champion; England's first sports superstar; the author of the first book on boxing theory, The Modern Art of Boxing (1789), and of the first sports memoir in history, The Memoirs of the Life of Daniel Mendoza (1813); and the first Jew to shake the hand of an English king. This article examines the role that three folkloric communications—a mock-heroic epic, The Odiad (1788 ); an epistolary sparring contest; and an urban popular ballad—played in shaping his public identity in the boxing community and, consequently, in shaping the place of Jews in late eighteenth-century Georgian social life.